Using images to extend smart object discovery in an Internet of Things scenario - Silva, Romulo; Viana, Windson; Dantas, Paulo Filipe (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2018)
The Internet of Things (IoT) represents a new paradigm in the Internet history and in the way people interact with everyday objects. Academics and several industry segments have been working over the past years to make this vision possible. It is estimated that there will be dozens or hundreds of devices simultaneously connected to the user’s network (e.g., in their home) in the next years, which can make the discovery and interaction with smart object more complicated to IoT users increasingly. This work proposes a smart objects discovery approach using image recognition, which aims to make this task quicker and more selective from an user perspective. An initial assessment has shown that the proposed mechanism can reduce the discovery time in a scenario with several devices, and additionally ensure a good level of user satisfaction.